Whole-transcriptome analysis of rat cavernosum and identification of circRNA-miRNA-mRNA networks to investigate nerve injury erectile dysfunction pathogenesis. Issue 1 (1st January 2021) - Huang, Jie; Ma, Jianxiong; Wang, Jie; Ma, Ke; Zhou, Kang; Huang, Wenjie; Zhao, Fan; Lv, Bodong; Hu, Qing
ABSTRACT: There is growing evidence that circular RNAs (circRNAs) play a vital role in many kinds of diseases, including erectile dysfunction (ED). Nevertheless, the role of circRNAs in cavernous nerve-damaging ED (CNI-ED) is unknown. Here, we aimed to discover novel circRNAs, probed their potential role in the CNI-ED, and construct a ceRNA network of circRNAs. Twelve male Sprague Dawley rats were randomly divided into 2 groups by us: bilateral cavernous nerve crush (BCNC) and control groups. Four weeks after surgery, the spongy smooth muscle tissue of the rat penis was sequenced using high-throughput full transcriptome sequencing. We analyzed the expression of circRNAs, miRNAs, and mRNAs in the two groups. Twenty circRNAs with significantly different expressions were selected for RT-qPCR. CeRNA network of circRNAs was established using Cytoscape. GO and KEGG analysis was done by R package. Sequencing showed that 4, 587 circRNAs, 762 miRNAs, and 21, 661 mRNAs were dysregulated in the BCNC group. The top 20 differentially expressed circRNAs were further verified via RT-qPCR. The ceRNA network contained ten circRNAs, six miRNAs, and 227 mRNAs, including 23 circRNA-miRNA pairs and 227 miRNA-mRNA pairs. GO and KEGG analysis suggested that these ten circRNAs could main regulate energy metabolism processes. A protein‐protein interaction network was constructed with the mRNAs in ceRNA network, and five hub genes were identified. Our study revealed a potential link between circRNAs, miRNAs, and mRNAs in CNI-ED, suggesting that circRNAs may contribute to the occurrence of ED by regulating the cellular energy metabolism in CNI-ED.